Polymorphisms Near TBX5 and GDF7 Are Associated With Increased Risk for Barrett's Esophagus. - O'Sullivan, Jacintha; Reynolds, John; Mc Manus, Ross (My University, 2015)
Barrett ’ s esophagus (BE) increases the risk of esophageal adenocarcinoma (EAC). We found the risk to be BE has been associated with single nucleotide polymorphisms (SNPs) on chromosome 6p21 (within the HLA region) and on 16q23, where the closest protein-coding gene is FOXF1 .Subse- quently, the Barrett ’ s and Esophageal Adenocarcinoma Con- sortium (BEACON) identi fi ed risk loci for BE and esophageal adenocarcinoma near CRTC1 and BARX1 , and within 100 kb of FOXP1 . We aimed to identify further SNPs that increased BE risk and to validate previously reported associations. METHODS: We performed a genome-wide association study (GWAS) to identify variants associated with BE and further analyzed promising variants identi fi ed by BEACON by genotyping 10,158 patients with BE and 21,062 controls. RESULTS: Weidenti fi ed2SNPsnot previouslyassociated with BE: rs3072 (2p24.1; oddsratio [OR] ¼ 1.14; 95% CI: 1.09 – 1.18; P ¼ 1.8 10 11 ) and rs2701108 (12q24.21; OR ¼ 0.90; 95% CI: 0.86 – 0.93; P ¼ 7.5 10 9 ). The closest protein-coding genes were respectively GDF7 (rs3072), which encodes a ligand in the bone morphogenetic protein pathway, and TBX5 (rs2701108), which encodes a transcription factor that regulates esophageal and cardiac development. Our dataalsosupported inBEcases3 riskSNPsidenti fi edbyBEACON (rs2687201, rs11789015, and rs10423674). Meta-analysis of all data identi fi ed another SNP associated with BE and esophageal adenocarcinoma: rs3784262, within ALDH1A2 (OR ¼ 0.90; 95% CI: 0.87 – 0.93; P ¼ 3.72 10 9 ). CONCLUSIONS: We identi fi ed 2 loci associated with risk of BE and provided data to support a further locus. The genes we found to be associated with risk for BE encode transcription factors involved in thoracic, diaphrag- matic, and esophageal development or proteins involved in the in fl ammatory response
PUBLISHED
Keywords: EAC, Intestinal Metaplasia, Susceptibility, Cancer; EAC, Intestinal Metaplasia, Susceptibility, Cancer; Genes & Society; Immunology, Inflammation & Infection; International Development